Facile Preparation of MnO2 Quantum Dots with Enhanced Fluorescence via Microenvironment Engineering with the Assistance of Some Reductive Biomolecules - Ma, Zhangyan; Sun, Yan; Xie, Jingwen; Li, Peipei; Lu, Qiujun; Liu, Meiling; Yin, Peng; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (ACS applied materials & interfaces, 2020)
MnO2 nanomaterials have aroused widespread attention because of their nanozyme activity, redox properties, good biocompatibility, and therapy-related activities. However, not many reports on self-luminescent MnO2 materials have been concerned to date, which greatly hampered their further development in various fields. In this paper, luminescent MnO2 quantum dots (MnO2 QDs) have been first prepared via a facile one-step ultrasonic method. With the assistance of bovine serum albumin (BSA) or cysteine (Cys), the synthesized MnO2 QDs (BSA-MnO2 QDs or Cys-MnO2 QDs) display strongly enhanced fluorescence (FL). The prepared BSA-MnO2 QDs with a particle size of about 1 to 2 nm show the maximum excitation and emission peaks at 320 and 410 nm with excellent salt stability, anti-photobleaching ability, and time stability. It is confirmed that BSA plays a dual function as the exfoliating agent to promote the exfoliation of bulk MnO2 nanosheets and as the capping agent to provide a friendly microenvironment for MnO2 QDs. Ag ions can destroy the microenvironment of BSA-MnO2 QDs owing to the in situ formation of Ag nanoparticles (Ag NPs) mediated by BSA on the surface of the QDs. Then, these Ag NPs can quench the FL intensity of the QDs by fluorescence resonance energy transfer. However, the FL strength of the BSA-MnO2 QDs is recovered after adding H2O2 and NaHS since they may react with Ag NPs to produce Ag+ and Ag2S, which further confirmed the role of BSA. This work not only opens up a facile and universal avenue to synthesize luminescent MnO2 QDs with enhanced FL but also provides a possible sensing platform through tuning the microenvironment of the MnO2 QDs. The MnO2 QDs with outstanding performance may show great potential as fluorescent probes in the fields of biological imaging, optical sensing, drug delivery, and therapy.